Analytical study of UHPC beam using truss model - Kho, William (Nanyang Technological University, 2021)
Ultra High Performance Concrete (UHPC) is an advanced concrete material with exceptionally high performance. Its exceedingly high performance is not limited to mechanical properties such as compressive strength and tensile strength. One of UHPC main materials is steel fiber which is used to increase tensile strength and tensile ductility. The advantage of UHPC tensile behavior is useful in many applications, where one of such application is on shear resistance of concrete structures. In reinforced concrete (RC) beam, steel stirrup is normally used to provide shear resistance. However, shear capacity is limited up to the maximum amount of stirrup provided. In this study, a truss model analogy is proposed to study the shear behavior of UHPC beams with shear span-to-depth ratio at least 2.0. The proposed truss model is based on variable angled truss model where UHPC tensile behavior is included into some of the tensile members of the truss model, especially the vertical truss members. The truss model is then validated with UHPC beam experimental result collected from literatures. After validation, a parametric study is conducted using 4 different variables namely shear span-to-depth ratio, UHPC compressive strength, longitudinal bottom rebar ratio, and steel fiber content. Steel fiber content is the main variable in this parametric study. Lastly, an equation is proposed to predict the shear capacity of UHPC beam. This study aims to propose a good prediction of truss model and a good shear capacity prediction equation, which ultimately answers “how much equivalent stirrup can UHPC provide as substitution?”